Human-nature interactions in the Afrotropics: experiential and cognitive connections among urban residents in southern Nigeria - Awoyemi, A.G.; Ibanez-Rueda, N.; Guardiola, J.; Ibanez-Alamo, J.D. (Elsevier, 2024)
Many people are losing direct contact with nature, a phenomenon termed as the extinction of experience. Urban dwellers are particularly affected by this process that influences public health and habitat conservation. We explored the extinction of experience among the urban populace in Nigeria, a clear Global South representative with rapidly increasing human population. We interviewed 600 adults from several cities and performed statistical tests. Results show that most respondents have no contact nor connection with nature, revealing an important distancing from the natural world. The reasons respondents gave for not experiencing nature more often are mainly related to material terms (e.g., lack of time, money and nearby natural areas). We found that respondents with higher nature contact are also more connected to nature, which is promoted by the perception of neighborhood safety. Respondents living in Lagos, and those with lower levels of income and education show greater dissociation from nature. The relationships between real and perceived neighborhood naturalness and bird species are decoupled, but the perception of naturalness and bird species richness correlates. Our study provides novel information on the loss of human-nature interactions and its determinants in the Afrotropics. We recommend different actions necessary to ameliorate this problem.